Collaboration to Enhance Culture and Arts on Pulau Ketam Malaysia as a Strengthening of Socio-Cultural Identity - Arissuta, Dona Prawita; Kholis, Achmad Nur (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Every region has areas that are far from the centre of government or the centre of community activity. Geographical conditions and social differences are the cause of the difficulty of a region to keep up with the times. This has an impact on the lagging of the community in various aspects ranging from the economy, cultural advancement, health, education, and so on. Pulau Ketam is a disadvantaged area located in Malaysia. The area is a coastal region that has limited access to be improved in all fields. There needs to be an effort to encourage the promotion of the community to maintain the socio-culture in the area. international community service activities are one solution that can be done. The method used in this community service activity is to identify problems in the field. The data found is then analysed to find solutions in community service activities. Activities related to art that are applied as an approach to the community and make a contribution are carried out in the form of collaboration. Fine art is part of a visual product that can be a medium to enter the community on Ketam Island. Repainting facilities and infrastructure using attractive images, holding open exhibitions, and art workshops are examples of means to maintain the community, especially related to the socio-cultural field. This is done to encourage the openness of the community to continue to improve progress from various fields that can become potential.